METHODS FOR DETERMINATION OF MICROPHYSICAL PARAMETERS OF NATIVE ERYTHROCYTES POPULATIONS - M. M. Kugeiko; D. A. Smunev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
The determination methods of the microphysical parameters of native erythrocytes populations by establishing stable regression relationships between the defined parameters and measured optical characteristics are developed. The possibility of creating a simple rapid analyzer of blood cells is shown.